Predicting the impact of pneumococcal conjugate vaccine programme options in Vietnam. Issue 8 (3rd August 2018) - Le Polain De Waroux, Olivier; Edmunds, W. John; Takahashi, Kensuke; Ariyoshi, Koya; Mulholland, E. Kim; Goldblatt, David; Choi, Yoon Hong; Anh, Dang Duc; Yoshida, Lay Myint; Flasche, Stefan
ABSTRACT: Although catch-up campaigns (CCs) at the introduction of pneumococcal conjugate vaccines (PCVs) may accelerate their impact, supply constraints may limit their benefit if the need for additional PCV doses results in introduction delay. We studied the impact of PCV13 introduction with and without CC in Nha Trang, Vietnam – a country that has not yet introduced PCV – through a dynamic transmission model. We modelled the impact on carriage and invasive pneumococcal disease (IPD) of routine vaccination (RV) only and that of RV with CCs targeting <1y olds (CC1), <2y olds (CC2) and <5y olds (CC5). The model was fitted to nasopharyngeal carriage data, and post-PCV predictions were based on best estimates of parameters governing post-PCV dynamics. With RV only, elimination in carriage of vaccine-type (VT) serotypes is predicted to occur across all age groups within 10 years after introduction, with near-complete replacement by non-VT. Most of the benefit of CCs is predicted to occur within the first 3 years with the highest impact at one year, when IPD incidence is predicted to be 11% (95%CrI 9 – 14%) lower than RV with CC1, 25% (21 – 30 %) lower with CC2 and 38% (32 – 46%) lower with CC5. However, CCs would only prevent more cases of IPD insofar as such campaigns do not delay introduction by more than about 6, 12 and 18 months for CC1, CC2 and CC5. Those findings are important to help guide vaccine introduction in countries that have not yet introduced PCV, particularly in Asia.